Event and fact as empirical objects of the French press discourse - Шевченко, Маргарита Юріївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The paper discusses the correlation between the notions of event and fact from the position of psycholinguistics, semantics, cognitive science, philosophy. The similarities and differences between these two notions were singled out. Also there were defined three types of event presentation in the information articles of the modern French media discourse: in the context of the associated events; out of this context; in comparison with the similar events. In the article headlines the event can be presented in a generalized, accurate or figurative way. On basis of quantitative analysis was singled out the most сommon type of the event presentation on the material of the French press headlines.